2013
DOI: 10.1016/j.joca.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The association between reduced knee joint proprioception and medial meniscal abnormalities using MRI in knee osteoarthritis: results from the Amsterdam osteoarthritis cohort

Abstract: This is the first study showing that reduced proprioceptive accuracy is associated with medial meniscal abnormalities in knee OA. The study highlights the importance of meniscal abnormalities in understanding reduced proprioceptive accuracy in persons with knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Of the 40 selected studies, 4 were prospective trials, [18][19][20][21] 16 were cohort-control designs, 11,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] and the remaining 20 were cross-sectional studies. 13,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Laxity was a primary variable of interest in 32 of the selected studies. Two studies received a quality assessment of poor with respect to the reporting of varus-valgus laxity in subjects with OA 23,24 due to a lack of detail on the method of objective laxity measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 selected studies, 4 were prospective trials, [18][19][20][21] 16 were cohort-control designs, 11,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] and the remaining 20 were cross-sectional studies. 13,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Laxity was a primary variable of interest in 32 of the selected studies. Two studies received a quality assessment of poor with respect to the reporting of varus-valgus laxity in subjects with OA 23,24 due to a lack of detail on the method of objective laxity measurement.…”
Section: Resultsmentioning
confidence: 99%
“…If proprioceptive impairments are explained by a generalized mechanism such as the overall quality of proprioceptive function for an individual or interference with memory/attention by pain, impairment should have presented for all joints tested. Isolation of proprioceptive impairment to the diseased knee joint is best explained by a localized phenomenon possibly related to local changes to mechanoreceptors (Hurley & Newham, 1993;van der Esch et al, 2013), processing/relay of somatosensory input to higher centers as reported in other conditions (Adkins, Boychuk, Remple, & Kleim, 2006;Liepert, Tegenthoff, & Malin, 1995;Napadow et al, 2006;Tsao, Galea, & Hodges, 2008;Wrigley et al, 2009), or joint-specific interference with cognitive processes associated with pain Hart et al, 2000;Schnurr & MacDonald, 1995). Although providing evidence of the mechanisms involved in local proprioceptive impairment in knee OA is beyond the scope of the current study it is reasonable to speculate on what these possible mechanisms may be in the context of generalized or localized impairment.…”
Section: Discussionmentioning
confidence: 99%
“…While a unifying model to explain the protective effect endowed by chronic exercise has not yet been established, researchers have identified possible factors that may contribute to its positive effect on joint health, including: greater knee stability, improved joint proprioception, and/or greater muscle strength (van der Esch et al 2013;Knoop et al 2013). An alternative, but not exclusive, hypothesis is that the joint loading associated with exercise promotes chondroprotection by altering the biochemical milieu of the intra-articular environment.…”
Section: Introductionmentioning
confidence: 99%